A meta‐analysis on employee perceptions of human resource strength: Examining the mediating versus moderating hypotheses. Issue 1 (31st May 2021) - Bednall, Timothy C.; Sanders, Karin; Yang, Huadong
Abstract: Human resource (HR) strength research has substantially informed an understanding of the relationship between HR practices and employee‐level outcomes. However, a key unresolved issue is whether employee perceptions of HR strength act as a mediator or a moderator in the relationship between HR practices and these outcomes. A meta‐analysis of 42 studies (comprising 65 samples and 29, 444 unique participants) was conducted to address this issue. Results support the mediating hypothesis for all five employee outcomes: employee reactions, proactive behavior, burnout, performance, and perceived organizational effectiveness. Conversely, the moderating hypothesis was only supported for employee performance. In addition, we examined five study characteristics (the operationalization of perceived HR strength, research study design, industry, sampling strategy, and publication status) as moderators. Using this analysis, we test the robustness of our main results and identify sources of heterogeneity in the results across studies. The results show that the mediating hypothesis still holds under different study designs and contexts. Theoretical and practical implications of these results are discussed.